2021
DOI: 10.1590/0103-6440202103384
|View full text |Cite
|
Sign up to set email alerts
|

Cortical Bone Modifications after Radiotherapy: Cortex Porosity and Osteonal Changes Evaluated Over Time

Abstract: Aiming to evaluate cortical bone microarchitecture and osteonal morphology after irradiation, twelve male New Zealand rabbits were used. The animals were divided: control group (no radiation-NIr); and 3 irradiated groups, sacrificed after: 7 (Ir7d); 14 (Ir14d) and 21 (Ir21d) days. A single radiation dose of 30 Gy was used. Computed microtomography analyzed the cortical microarchitecture: cortical thickness (CtTh), bone volume (BV), total porosity (Ct.Po), intracortical porosity (CtPo-cl), channel/pore number (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 22 publications
0
1
0
Order By: Relevance
“…The heterogeneity of the osteon morphology following irradiation has been reported in an animal study. 22 The difference in the osteon sizes and morphology was evident in our study groups. The lamellar organization around the HCs was evident in our control and many irradiated samples both under LM and SEM.…”
Section: Discussionmentioning
confidence: 59%
“…The heterogeneity of the osteon morphology following irradiation has been reported in an animal study. 22 The difference in the osteon sizes and morphology was evident in our study groups. The lamellar organization around the HCs was evident in our control and many irradiated samples both under LM and SEM.…”
Section: Discussionmentioning
confidence: 59%
“…( 68 ) Interestingly, timed analysis of rabbit tibias (7, 14, 21 days) post‐exposure to a single dose of 30 Gy showed that the majority of impacted cortical parameters, including porosity, recovered to non‐irradiated levels 14 and 21 days post‐exposure, suggestive of a potential correlation between bone turnover recovery and time post‐exposure. ( 69 ) Although the rabbits in our study had the added variable of PTH treatment, their cortices were subjected to non‐therapeutic radiation doses and assessed after a shorter period (14 days) post in vivo imaging, which may explain why we found little evidence of significant radiation dose effects. Notably, in this study, we only reported the incident dose; however, since the synchrotron beam utilized here was monoenergetic, the absorbed dose in the bone tissue here is less than the case of polychromatic X‐ray beam from X‐ray tube sources.…”
Section: Discussionmentioning
confidence: 96%
“…This indication is based on the progressive process of connective tissue fibrosis that reduces the vascularization, cellularity and oxygenation of oral tissues, especially bone tissue, which can impair the repair processes 5,12,13,28 . The bone tissue has the slower regenerative potential than soft tissues 2,5,14,28 . During the healing phase, especially the post-extraction alveolar repair occurred by second intention, makes this tissue more susceptible to contamination and subsequent development of necrotic lesions, which are difficult to treat 2 .…”
Section: Discussionmentioning
confidence: 99%
“…Ionizing radiation produces hypoxia, hypocellularity and hypovascularization that can alter the regenerative potential of the soft and hard tissues 2,13,14 . Changes in tooth and bone structure can occur due to degradations in amine components that can mechanically alter enamel 15,16 , dentin 12 , and bones 14,15,17 .…”
Section: Dental Procedures After Rtx Treatmentmentioning
confidence: 99%
See 1 more Smart Citation